2021
DOI: 10.3390/su13042226
|View full text |Cite
|
Sign up to set email alerts
|

One Year Residual Effect of Sewage Sludge Biochar as a Soil Amendment for Maize in a Brazilian Oxisol

Abstract: The thermochemical transformation of sewage sludge (SS) to biochar (SSB) allows exploring the advantages of SS and reduces possible environmental risks associated with its use. Recent studies have shown that SSB is nutrient-rich and may replace mineral fertilizers. However, there are still some questions to be answered about the residual effect of SSB on soil nutrient availability. In addition, most of the previous studies were conducted in pots or soil incubations. Therefore, the residual effect of SSB on soi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 17 publications
(8 citation statements)
references
References 64 publications
2
6
0
Order By: Relevance
“…Compared with biochar from multiple feedstocks [19] and with other types of soil amendments [20], SSB has higher P levels, with great potential for use as a P fertilizer. Increases of Ca, Mg, S and micronutrients levels have also been reported in previous studies with SSB at 300ºC [8,17,21].…”
Section: Physical and Chemical Characteristicssupporting
confidence: 82%
See 2 more Smart Citations
“…Compared with biochar from multiple feedstocks [19] and with other types of soil amendments [20], SSB has higher P levels, with great potential for use as a P fertilizer. Increases of Ca, Mg, S and micronutrients levels have also been reported in previous studies with SSB at 300ºC [8,17,21].…”
Section: Physical and Chemical Characteristicssupporting
confidence: 82%
“…The increase in ash content is expected, since up to 600°C most of the mineral material is preserved and volatile compounds are lost, resulting in a higher ash concentration [15]. The pH value was not altered by pyrolysis and it was close to neutrality (6.5), similar to results previously reported for biochars obtained at low temperatures (300ºC) [7,8]. Typically, increases in pH are observed at higher pyrolysis temperatures (> 400°C).…”
Section: Physical and Chemical Characteristicssupporting
confidence: 82%
See 1 more Smart Citation
“…Fading effect of biochar after multiple seasons might be attributed to leaching of alkali metals from biochar, signifying the need of reapplication of biochar. Similarly, Fachini et al (2021) found that positive effect of biochar on crop growth faded over time in an acidic soil of Brazil. Conversely, a few studies demonstrated biochar's positive effects on crop yield from second season onwards, indicating the effect of biochar aging on nutrient retention and supply to plants (Major et al, 2010;Griffin et al, 2017).…”
Section: Biochar-induced Crop Productivity In Weathered Soilsmentioning
confidence: 89%
“…Similarly, Fachini et al also found that the addition of sewage sludge biochar significantly promoted P uptake and maize yield in a three-year consecutive corn cropping system. 54 Figure S7 reveals that in original red soil, paddy soil, and yellow soil, the P uptakes of corn, rice, and wheat were approximately 1, 3, and 1.5 mg per pot as the unit, respectively. However, with the addition of SSBC, the P uptakes of the three plants increased to 4, 7, and 1 mg, respectively.…”
Section: ■ Results and Discussionmentioning
confidence: 99%